Perbandingan Antara Mahasiswa Aktivis dan Bukan Aktivis Dalam Sikap Terhadap Kuliah dan Perilaku Assertif di UIN Jakarta - Kokom Komariah (‎‎‎TAZKIYA Journal of Psychology, 2003)
Students are a topic that is always interesting to discuss because students have a big role in criticizing things that are wrong. In Indonesia, students also have a role in achieving Indonesian independence. With students actively participating in activist activities and the presence of influences from outside the lecture, it is possible for external factors to emerge that will be attached to them. Not all students take part in activist activities, there are also students who are apathetic towards these activities. Therefore, this research was conducted to find out whether there were differences between students who took part in activist activities and those who did not.